P5_6 Defrosting Mars with ”a Few” Mirrors - Shaikh, Hasan; Agrawal, Rusi; Ruprai, Amrik; Singh, Jagraj (Physics Special Topics, 2021)
The minimum power that can be redirected to the Martian surface by a ‘3M VM2000’ concave reflector, with a diameter of 8 km, is of the order 10^10 W, from which 1000 satellites in orbit would be able to melt, at least, the 5 million km^3 of known surface polar ice sheets, in under 10^5 years, but the manufacturing of such reflectors were found to be financially infeasible.